ANALISIS KINERJA KEUANGAN PERUSAHAAN DENGAN MENGGUNAKAN METODE ECONOMIC VALUE ADDED (EVA) (KASUS PADA PERUSAHAAN INDUSTRI MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Novia Islan; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research aims to know financial performance at four sector of the food and beverage industry companies that is with sub-sectors PT. Delta Djakarta Tbk, PT. Indofood Sukses Makmur Tbk, PT. Mayora Indah Tbk and PT. Ultrajaya Milk Industry and Trading Company Tbk during 2012 until 2014 by using a method of Economic Value Added (EVA). The research as descriptive of a quantitative approach by using capital structure analysis, WACC analysis, NOPAT analisys, ROIC analysis and EVA analysis. This research shows that the results the analysis of financial performance by using a method of Economic Value Added (EVA) during 2012 until 2014 the condition of financial PT. Delta Djakarta Tbk show a positive value but occur fluctuation. While at PT. Ultrajaya Milk Industry and Trading Company Tbk the financial condition of the company in the year 2012 until 2014 an increase and a positive value. But different with PT. Indofood Sukses Makmur Tbk and PT. Mayora Indah Tbk the condition of the financial performance of companies using method of Economic Value Added (EVA) experiencing negative value every years.Key words : Financial Performance, Economic Value Added (EVA) Method’s